The crime of the so-called prenatal injury and the question of non-punishability of the mother of a conceived child - Sobiech, Jan (The Opole Studies in Administration and Law, 2021)
The article considers the crime of the so-called prenatal injury, which is stipulated in Article 157a of the Polish Criminal Code. The question of the possibility of unpunished interference of the mother in the body of her unborn child is undoubtedly an important and controversial aspect of modern criminal law, especially in the context of the principles of protecting human life and health. The article also touches on philosophical and legal subjects, namely the moment when a person is created and subsequently protected by the state and law. Finally, the article answers the question whether the current legal status should be maintained and how it could possibly be revised.